(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
The work by Sampaio, Sabbatini, and Limongi highlights the effects of generative Artificial Intelligence on academic research. It aims to serve as a starting point for considering guidelines on the subject. Based on the understanding that researchers must understand how this technology works to use it critically, ethically, and effectively, the book offers practical recommendations on utilizing the tools without compromising necessary precautions. The review emphasizes the following points covered in the guide: i) the controversies over the mythological view of AI; ii) the westernized biases of AI; iii) the inevitability of human-in-the-loop work; iv) the need for researchers to be literate; v) the issue of national sovereignty; vi) exposure of the declaration of the use of IAG in work; and vii) the benefits and potential for innovation of AI in scientific production.